KONTAMINASI BAHAN PLASTIK PADA JAJANAN PASAR (GORENGAN) YANG BEREDAR DI KOTA MEDAN - Dita Sari; Riyanto Riyanto; Abdul Karim (Universitas Medan Area, 2017)
This reseach aims to know the contamination of plastic materials that exist in market snacks (fried banana, fried tempe, fried tofu and bakwan goreng) that circulated in Medan City. This research uses the method of